PERLINDUNGAN HUKUM BAGI FRANCHISOR TERHADAP FRANCHISEE YANG MELAKUKAN PELANGGARAN HAK MEREK - Pradnya Pramita, Anak Agung Ayu Dwi Cahya; Dian Sawitri, Dewa Ayu (Kertha Negara : Journal Ilmu Hukum, 2023)
The study conducted aims to determine and analyze the elements of intellectual property rights contained in a franchise agreement and legal protection to the franchisor against franchisees who violate trademark rights. There are several types of research that can be used to assess the problem, namely normative research through a statutory approach. The results of this study explain that the elements of intellectual property rights contained in franchise agreements are trademark rights, patents, copyrights, and trade secrets. In addition, settlements against franchisees who violate trademark rights can be carried out in litigation and non-litigation have been regulated in Article 83 and Article 93 of Law Number 20 Th. 2016 concerning Marks and Geographical Indications.Keywords : Franchisee, Intellectual Property Rights, Brand